On species groups in the jumping spider genus Hypaeus Simon, 1900 (Araneae: Salticidae: Amycini), with a revision of the H. porcatus species group - Borges, Jeynne Pimentel; Ruiz, Gustavo R.s. (Zootaxa, 2026)
Hypaeus Simon, 1900 is one of the most diverse genera of Amycini, but its limits and internal structure remain poorly defined. Herein, we focus on species closely related to the type species H. taczanowskii (Mello-Leitão, 1948) and propose four species groups within Hypaeus based on shared morphological traits: the H. taczanowskii, the H. miles, the H. ignicomus, and the H. porcatus species groups. The H. porcatus species group is revised in detail. Fresh males of H. flavipes Simon, 1900, H. frontosus Simon, 1900, and H. porcatus (Taczanowski, 1871) are described, and their unknown females are described for the first time. Dasyophrys nigra Mello-Leitão, 1930 is revalidated, and Dasyophrys Mello-Leitão, 1930 is confirmed as a junior synonym of Hypaeus. Maenola lunata Mello-Leitão, 1940 is synonymized with H. niger comb. nov., which is redescribed based on both sexes. Noegus lodovicoi Ruiz & Brescovit, 2008 and Agelista petrusewiczi Caporiacco, 1947 are transferred to Hypaeus. Hypaeus lodovicoi comb. nov. is proposed as a junior synonym of H. frontosus. The female of Hypaeus petrusewiczi comb. nov. is redescribed and the male is described for the first time. Hypaeus tapajonicus sp. nov. is described from Brazil based on males and females. Detailed description of cheliceral dentition in the H. porcatus species group is given. These four species groups are interpreted as composing Hypaeus sensu stricto, whereas the placement of other species currently assigned to the genus remains to be tested in future comparative or phylogenetic studies.